Pseudomonas syringae on plants in Iceland has likely evolved for several million years outside the reach of processes that mix this bacterial complex across Earth's temperate zones - Morris, Cindy E.; Ramirez, Natalia; Berge, Odile; Lacroix, Christelle; Monteil, Cécile; Chandeysson, Charlotte; Guilbaud, Caroline; Blischke, Anett; Sigurbjörnsdóttir, Margrét Audur; Vilhelmsson, Oddur (Pathogens, 2022)
International audience Here we report, for the first time, the occurrence of the bacteria from the species complex Pseudomonas syringae in Iceland. We isolated this bacterium from 35 of the 38 samples of angiosperms, moss, ferns and leaf litter collected across the island from five habitat categories (boreal heath, forest, subalpine and glacial scrub, grazed pasture, lava field). The culturable populations of P. syringae on these plants varied in size across 6 orders of magnitude, were as dense as 107 cfu g−1 and were composed of strains in phylogroups 1, 2, 4, 6, 7, 10 and 13. P. syringae densities were significantly greatest on monocots compared to those on dicots and mosses and were about two orders of magnitude greater in grazed pastures compared to all other habitats. The phylogenetic diversity of 609 strains of P. syringae from Iceland was compared to that of 933 reference strains of P. syringae from crops and environmental reservoirs collected from 27 other countries based on a 343 bp sequence of the citrate synthase (cts) housekeeping gene. Whereas there were examples of identical cts sequences across multiple countries and continents among the reference strains indicating mixing among these countries and continents, the Icelandic strains grouped into monophyletic lineages that were unique compared to all of the reference strains. Based on estimates of the time of divergence of the Icelandic genetic lineages of P. syringae, the geological, botanical and land use history of Iceland, and atmospheric circulation patterns, we propose scenarios whereby it would be feasible for P. syringae to have evolved outside the reach of processes that tend to mix this bacterial complex across the planet elsewhere.